2016
DOI: 10.1515/amm-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Manufacturing Bimetallic Tubes by the Cold Drawing Process

Abstract: Drawing processes apply to obtain the bimetallic tubes from the different metals and alloys, combined in the solid state, which significantly affects the specificity of this process. The manufacturing of bimetallic tubes by drawing process depends on many factors which include: preparation of the surface of materials joined in the solid state, the geometric parameters of the working tool, technological parameters of the drawing process (drawing speed, type of lubricant, the use of back pull etc.). Generally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The experimental values of the total strain εtotal, the bulk elastic modulus E, and the apparent elastic modulus E' are substituted into Equation (15). The plastic strain obtained by Equation ( 15) generally agrees with the value obtained from Equation (9). Therefore, the unloading behavior can be expressed by a quadratic approximation.…”
Section: Excessive Thinning Of the Outer Diameter After Drawingsupporting
confidence: 58%
See 1 more Smart Citation
“…The experimental values of the total strain εtotal, the bulk elastic modulus E, and the apparent elastic modulus E' are substituted into Equation (15). The plastic strain obtained by Equation ( 15) generally agrees with the value obtained from Equation (9). Therefore, the unloading behavior can be expressed by a quadratic approximation.…”
Section: Excessive Thinning Of the Outer Diameter After Drawingsupporting
confidence: 58%
“…In this study, tubes with a maximum outer diameter of 2 mm, which are required for several applications [5], were defined as the microscale tubes. Generally, the outer diameter of a macroscale drawn tube, such as an outer diameter of about 20 mm, matches the die diameter [9]. However, the authors reported that the outer diameter of the microscale drawn tubes with the outer diameter of about 1.5 mm became smaller than the die diameter starting from the die approach end [10].…”
Section: Introductionmentioning
confidence: 98%
“…Based on increasing demand to improve performance while reducing weight, the use of bimetal tubing is becoming more widely used in the aerospace, nuclear energy, and automotive and petrochemical industries. At the present time, bimetal tubes are mainly produced and fabricated using processes which includes hydraulic bulging [1], hot extrusion [2], hot rolling [3], mechanical drawing [4], explosive welding [5], as well as other plastic forming techniques by centrifugal casting methods [6], electromagnetic forming method [7], etc. Yet the above forming methods have some problems such as complex structure and low flexibility of the tooling.…”
Section: Introductionmentioning
confidence: 99%